Keefektifan Video Animasi Untuk Meningkatkan Interaksi Sosial Antar Teman Sebaya Pada Kelompok B Paud Dara Itam Ngabang - Nia Daniawati; Yohanes Bahari; Halida Halida; Herry Sujainni; Ahmad Yani (Jurnal Ilmiah Global Education, 2026)
Peer social interaction is an important aspect of early childhood social and emotional development. However, some children still experience difficulties in interacting, such as limited communication skills, low cooperation ability, and lack of participation in group activities. This study aims to determine the effectiveness of using animated videos to improve peer social interaction among Group B children at PAUD Dara Itam Ngabang. The study employed a quantitative approach with an experimental method using a one-group pretest–posttest design. The research subjects consisted of 24 children. Data were collected through observation using a social interaction assessment sheet and analyzed using the Wilcoxon Signed Rank Test. The results showed an improvement in children’s social interaction across all observed indicators after the implementation of animated videos, with a significance value of 0.000 (p < 0.05), indicating a significant difference between pre-test and post-test results. Therefore, animated videos are proven to be effective as a learning medium to improve peer social interaction in early childhood.